Barriers for Adopting Artificial Intelligence in Digital Marketing of SMEs - Mohammed ENSHASSI; Robert Jeyakumar NATHAN; Hishamuddin ISMAIL; Maria KOLESOVA (Communications of International Proceedings, 2022)
Purpose: This study addresses the barriers SMEs face when adopting AI in digital marketing. Design/methodology/approach: The study is based on an extensive literature review conducted through the lens of the extended Technology-Organization Environment (TOE) framework. Findings: Literature review highlights several significant barriers to AI adoption relating to technology, organization, environment, and data in SMEs. AI technologies are promising for SMEs' growth and performance; however, the apparent and perceived barriers faced by SMEs hinder AI adoption in their digital marketing efforts. Practical implications: This study is useful for SME researchers who aim to escalate SME marketing performance with new advancements in technology, particularly the usage of AI for business and digital marketing. Originality/value: Numerous studies have addressed the barriers to adopting AI in various sectors. However, the barriers to adopting AI in digital marketing for SMEs are not well researched; thus, this study focuses on this area of study. This paper presents an integrated framework for an empirical study to quantify the barriers to AI adoption in SME digital marketing.
Keywords: Technology Barriers; TOE framework; Electronic Commerce; Digital Marketing.